Pengembangan Sistem Perangkat Lunak Administrasi Pasien Berbasis Mobile (Studi Kasus : Sanggar Sehat Gurubansa) - Widia; Waluyo, Anita Fira (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Sanggar sehat Gurubansa patient administration system application is a software application designed to manage the administrative data of Sanggar Sehat Gurubansa to be more structured and organized. The administration system here is in the form of managing Sanggar patient data, medical records and payments. The purpose of this research is to develop the administration system of Sanggar Sehat Gurubansa by replacing the manual handwriting process with a mobile-based system. The system development method used at this time is the waterfall method. The waterfall method is a step that must be done sequentially one by one (cannot move on to the next part before the part being worked on is complete). The data collection methods applied in the administrative management process of Sanggar Sehat Gurubansa are interviews, location surveys, and literature studies while the system testing method uses blackbox analysis. This program was developed using several tools, including Android Studio, XAMPP, VSC and MySQL as the database. So that in the end the application developed can provide the information needed by users of the Sanggar Sehat Gurubansa quickly and efficiently.